2011
DOI: 10.1186/1745-6215-12-169
|View full text |Cite
|
Sign up to set email alerts
|

INVESTIGATE-I (INVasive Evaluation before Surgical Treatment of Incontinence Gives Added Therapeutic Effect?): study protocol for a mixed methods study to assess the feasibility of a future randomised controlled trial of the clinical utility of invasive urodynamic testing

Abstract: BackgroundUrinary incontinence is an important health problem to the individual sufferer and to health services. Stress and stress predominant mixed urinary incontinence are increasingly managed by surgery due to advances in surgical techniques. Despite the lack of evidence for its clinical utility, most clinicians undertake invasive urodynamic testing (IUT) to confirm a functional diagnosis of urodynamic stress incontinence before offering surgery for this condition. IUT is expensive, embarrassing and uncomfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…This confirmed that all employed similar procedures in relation to screening, in adherence with that laid out in the study protocol [5]. It was nonetheless possible that, although procedures were standardised and adhered to, variability in assessment of potential eligibility amongst recruiting staff may have resulted in variations in screening and recruitment.…”
Section: Introductionsupporting
confidence: 60%
“…This confirmed that all employed similar procedures in relation to screening, in adherence with that laid out in the study protocol [5]. It was nonetheless possible that, although procedures were standardised and adhered to, variability in assessment of potential eligibility amongst recruiting staff may have resulted in variations in screening and recruitment.…”
Section: Introductionsupporting
confidence: 60%
“…There are several reasons to conduct a pilot trial and feasibility assessment before undertaking a definitive trial of IUT prior to surgery for SUI or stress predominant MUI. These were reviewed in the background to the published protocol for this study 14. The INVESTIGATE‐I study was therefore planned as a mixed methods study looking at the feasibility of a definitive trial of the clinical and cost‐effectiveness of IUT prior to surgery for SUI or stress predominant MUI 15.…”
Section: Introductionmentioning
confidence: 99%
“…Ninety‐one studies were considered but 83 were excluded because they did not randomize patients to at least one type of urodynamic investigation or one method of performing a urodynamic investigation. One other trial is ongoing …”
Section: Resultsmentioning
confidence: 99%
“…One new trial among women is in progress and has completed recruitment in January 2013 (attaining 222 participants of a targeted 240) . It is possible, when results are available, that the findings of this trial may produce robust, reliable evidence.…”
Section: Discussionmentioning
confidence: 99%